Sistem Informasi Absensi Siswa Berbasis Web Menggunakan Framework Laravel 9 dan RFID Arduino Pada SMKN 9 Medan - Muhammad Zen; Rian Farta Wijaya; Irwan (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
Absence is a routine activity carried out by students every time they carry out learning activities. The attendance process at school is generally still done manually. So it takes a lot of time to learn and teach. Arduino is an open source technology. So that research was carried out related to this Radio Frequency Identification or RFID Arduino based attendance system. RFID has advantages over other attendance methods. This advantage is that there is no need to bring in students to record initial data like in the others. Furthermore, a web-based information system functions to manage student attendance. This information system was built using the PHP programming language and the Laravel framework. Laravel is a PHP framework that has functions to facilitate the development of web-based applications. Apart from that, Laravel also has a good application security system. So in this study the authors tried to develop an Arduino and Laravel RFID-based student attendance system as an attendance management application for admins. After doing research, PHP cannot read data via serial port directly. Therefore we need an additional desktop-based application. The desktop-based attendance application functions to retrieve data from Arduino and perform attendance to the database. The attendance process begins with the input of meeting material by the teacher. Based on the last meeting the teacher input the absence process by RFID is carried out. The results of this study are that the system can only handle one class for an Arduino RFID device.